The transformation’s potential and the earth construction’s promotion in vulnerable societies (2019)
However the uncountable advantages that the earth construction may provide even in current times, it is undeniable the condition of an historical lost of the traditional and popular building pieces of knowledge of the societies that made use of it, not only due to economical and social reasons, but as well as political and cultural too. Taking this in consideration, of a conditioning of those architectonic practices under the most diverse elements of reality, the practical viability of an actual adoption of the earth as a building material in informal and vulnerable contexts, will only be possible through a scientific approach that is capable of answering those multiples circumstances whilst motivating the participants in a state and perspective of self-determination and of overcoming any sort of limitations. Aiming at focusing the social and political potential that the participative and interested learning of this technology as an organized collective may promote, in this work we will have as an objective the demonstration, using of theoretical and practical studies and based in the analyses of a particular situation, that the rescue and resignification of the earth as a building medium from an historical contextualization executed by the group members is capable of contributing, evidencing and positioning this theme under a different perspective. The analyses performed made possible to assert that eventual conflictive relations that, in different perspectives and pedagogical dynamics would limit an actual appropriation of a building knowledge through a collective process, may result in itself in a potential catalyzer of transformation, from the dialogue of the differences and assuming a political position in the learning process and of self affirmation for a new society.